A history of modern Tibet. - Goldstein, Melvyn C. (University of California Press, 2019)
"It is not possible to understand contemporary politics between China and the Dalai Lama without understanding what happened in the 1950s, especially the events that occurred in 1957-59, which is the subject of the fourth and final volume of Melvyn C. Goldstein's quartet on the History of Modern Tibet. Volume 4 provides new perspectives on Sino-Tibetan history during the period leading to the Tibetan Uprising of 1959, and reassesses important issues and stereotypes that have been widely misunderstood or misrepresented in both the popular realm and the academic literature (such as Mao's policies on Tibet). Volume 4 draws on important new Chinese government documents, published and unpublished memoirs, new biographies, and a large corpus of in-depth political interviews collected specially for this history series to reexamine and reevaluate the events that produced the March 10th uprising and the demise of Tibet's famous Buddhist civilization. The result is a heavily documented analysis that presents a nuanced and balanced account of the principal players and their policies during the critical final two years of Sino-Tibetan relations under the 17-Point Agreement of 1951"--Provided by publisher